(untitled) (Third Sector Social Economic Review, 2026)
The success of digital transformation depends on the extent to which an organization adopts this process as a legitimate change compatible with its own structure. Within the framework of new corporate theory, leadership is considered an element integrated with organizational values and beliefs, and therefore, leadership also needs to be transformed at the strategic level in parallel with digitalizing structures. Digital transformation has become a strategic factor affecting not only operational processes but also investment decisions. In this context, digital transformation leadership contributes to the shaping of investment decisions based on digitalization by creating a rationality that directs transformation within the organization. This study examines the relationship between digital transformation leadership and investment decisions and aims to test whether digital transformation plays a mediating role in this relationship. The research model was tested using partial least squares structural equation modeling (PLS-SEM) with the SmartPLS software package. The study sample consists of 112 senior managers working in companies operating in the service and manufacturing sectors in Istanbul, Turkey. The findings of analysis show that digital transformation leadership is positively correlated with both digital transformation perception and investment decisions. Furthermore, the findings reveal that digital transformation perception is positively correlated with investment decisions and plays a partial mediating role in the relationship between digital transformation leadership and investment decisions. In this context, the results demonstrate that not only investing in technology but also adopting transformational leadership approaches is important for increasing the impact of digitalization on decision-making processes.